Pengaruh Intervensi Model Dukungan Sebaya Santri Husada terhadap Kemampuan Penerapan Perilaku Hidup Bersih dan Sehat Penghuni Pesantren - Yeti Resnayati; Eska Riyanti; Raden Siti Maryam (Jurnal Keperawatan, 2023)
The problems continue happened in the boarding school in life santri is fulfillment Behavior Life Clean and Healthy (PHBS) less adequate so that raises problem disease especially disease related diseases with lack of cleanliness self (personal hygiene) like disease skin and diarrhea or infection channel breathing . This Research aimi for describe influence application of the model of peer group support santri husada to ability application behavior life clean and healthy (PHBS) on occupants boarding school. The model of peer group support santri husada is an innovative approach that is important for shaping individual perceptions and behavior formation Design Research use quasi- experimental with approach design pretest-posttest control group. The sampling strategy uses Simple Random Sampling with a large sample using a test formula different two proportion so that total sample, group intervention or group control are 41 people. Data analysis is done with stages univariate and bivariate with Paired T-Test, as well as Independent T Test. Research results showed there are significant differences (p = 0.000) in knowledge, attitudes and behavior in application PHBS between group intervention and group control after do peer support model intervention in PHBS. It is hoped that the role of Islamic boarding school leaders will be in strengthening their students to carry out PHBS in their daily lives.